Bibliometric Analysis of the New Paradigm of Human Resource Management in Indonesian State Islamic Universities (2000-2025) - Susilo Surahman; Burhanuddin; Rudi Hartono; Barkatillah; Chusna Maulida; Purniadi Putra (Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2026)
The paradigm of human resource management (HRM) is rapidly evolving in the digital era, requiring adaptive frameworks, particularly within higher education institutions. This study aims to analyze the emerging HRM paradigm in State Islamic Universities and identify key research trends and thematic structures. Using a quantitative bibliometric approach, 746 articles indexed in Scopus and Web of Science were collected through Publish or Perish and analyzed using VOSviewer. The results reveal five major clusters, with Economics and HRM as the most dominant themes, indicated by high keyword co-occurrence and link strength. Recent trends show a shift from purely theoretical discussions to more practice-oriented, technology-driven topics, particularly the integration of artificial intelligence into HRM. Despite this development, research specifically addressing the contextual implementation of HRM systems in Islamic higher education remains limited. This study contributes by mapping the intellectual structure, highlighting the emerging role of AI as a key element in shaping a new HRM paradigm within Islamic State Universities, and identifying future research directions that bridge theory and practice.